THE EVALUATION OF QUALUTY GOALS AT THE PROCESS LEVEL IN AN UNCERTAIN ENVIRONMENT - Puškarić, Hrvoje Ž (Journal of Applied Engineering Science, 2013)
Improvement of business processes is achieved, among the other, through improvement of quality goals which are defined on the level of each process. In practice, it is not possible to improve all identified quality goals simultaneously. It is assumed that it is necessary that the quality goals values be determined by applying determined metrics. With respect to given values of quality goals, management team determines the order by which quality goals are improved. In this paper, the relative importance of quality goals are stated by fuzzy pair-wise comparison matrix. The performances of quality goals are described by linguistic expressions. All linguistic expressions are modelled by triangular fuzzy numbers. The new model for evaluation of quality goal values with respect to their relative importance is proposed. The developed model is tested by illustrative example with real life data of development process.3. Keywords: quality goals, fuzzy sets, evaluation